The practice and plants used in Besale ritual healing by the Anak Dalam Tribe in Nyogan Village, Jambi, Indonesia - Revis Asra; Marina Silalahi; IZU ANDRY FIJRIDIYANTO (Society for Indonesian Biodiversity, 2020)
Abstract. Asra R, Silalahi M, Fijridiyanto IA. 2020. The practice and plants used in Besale ritual healing by the Anak Dalam Tribe in Nyogan Village, Jambi, Indonesia. Biodiversitas 21: 4529-4536. The Anak Dalam Tribe (ADT) is an indigenous ethnic which inhabits the center of Sumatra, especially in Jambi and South Sumatra Provinces, Indonesia. The ADT communities still maintain their traditional rituals; one of them is the Besale ritual healing (BRH). This study aims to analyze the diversity of plants used in BRH by the ADT in Nyogan Village, Jambi Province, Indonesia. The study was conducted with an ethnobotany approach through surveys using interviews and participatory observations. The total number of informants was six persons, namely the leaders and performers of the BRH. The data were analyzed qualitatively using descriptive statistics. The BRH is carried out by a dukunorsidi (shaman), bujang pembayun (dancers), biduan (singers), and inang (assistant). They combine ritual and treatment simultaneously to cure people who have severe illnesses. There are 21 species belong to 20 genera and 12 families of plants used in the BRH. The plants are used to build a hall (place for the BRH),